Association of the calcitriol to calcifediol ratio with cardiac involvement in newly diagnosed sarcoidosis - Giallafos, Elias; Kolilekas, Lykourgos; Manali, Effrosyni; Katsanos, Spyros; Steiropoulos, Paschalis; Tsougos, Elias; Stratakos, Grigorios; Gaga, Mina; Koulouris, Nikos; Papiris, Spyros; Ilias, Ioannis (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Vitamin D (VitD) has been shown to influence many diseases, including sarcoidosis (Sa) and cardiovascular diseases with decreasing levels of vitamin being correlated with increased mortality. A possible association between VitD metabolites with cardiac involvement in patients with Sa which impairs prognosis, even with preserved left ventricular ejection fraction (EF) has not been seen. Aim of this study was to evaluate serum 1,25(OH)2D3, 25(OH)D3 and their ratio (VDR) with myocardial involvement in Sa. Methods-Results: 87 newly diagnosed sarcoidosis patients in two groups of cardiac (GroupB) and non-cardiac (Group A) involvement were studied for serum serum 25(OH)D3 and 1,25(OH)2D3 levels. Laboratory and clinical features including pulmonary and cardiac function parameters were collected. The 21 patients forming group B had significantly higher body mass index (BMI) (27.09±5.14vs30.06±4.63 p=0.013), lower EF (63.26±3.54vs60.9±4.36, p=0.009), higher 25(OH)D3 (19.44±9.99vs24.19±8.84, p=0.039) and lower VDR (1.6±0.84vs1.16±0.33, p=0.0001). Logistic regression was performed to ascertain the effects of BMI, EF, VDR on the likelihood that subjects had cardiac involvement. The logistic regression model was statistically significant (Chi square=21.257, p=0.0001). The obtained model correctly predicted 80.82% of cases. For each incremental increase in VDR or EF subjects were 5.55 or 1.22 times less likely to exhibit cardiac involvement, respectively, whereas for each incremental increase in BMI subjects were 0.78 times more likely to exhibit cardiac involvement. Conclusion: The role of Vit D metabolites and especially VDR may represent a promising simple informative tool for initially assessing cardiac involvement in Sa; worth to be further evaluated in the future.